Disparities in Jurisdictional Locus Between the Enforcement of Maritime Immigration and Customs Laws Based on the Provisions of UNCLOS 1982 Through an Analysis of Lawrence M. Friedman's Legal System Theory - Muhammad Choirul Yusuf; M. Alvi Syahrin; Ridwan Arifin (Jurnal Ilmiah Dunia Hukum, 2026)
Indonesia's geographical location at the intersection of two continents and oceans makes it a strategic consideration in assessing maritime development potential. To achieve maritime security resilience oriented toward the management and efficiency of maritime resources, the existence of law enforcement and legal substance in maritime zones is necessary to formulate legal certainty. The parent legal provisions governing maritime zone provisions and management rests on Law Number 17 of 1985, which ratified UNCLOS 1982, with its 320 articles and 9 annex. Among the various maritime zone provisions, there is the term "contiguous zone," which is a special jurisdiction extending 24 miles from the regulated sea baseline and serves as the basis for Immigration, Customs, Fiscal, and Sanitary Affairs to conduct supervision related to its legal provisions. However, the regulation of contiguous zones or maritime area specifications has not been accommodated in Law Number 6 of 2011 concerning Immigration as a form of active supervisory function, while Law Number 17 of 2006 concerning Customs has long accommodated provisions providing concrete supervision. This paper aims to analyze the harmonization of legislation, historical, and empirical aspects related to legal considerations regarding the formulation of articles regulating the locus of jurisdiction for maritime immigration supervision, thereby providing an ideal legal formulation within the framework of academic studies. The research method used in this paper is a normative-empirical one. The theory in this study applies Lawrence Friedman's legal system theory as an analytical tools. The results also indicate the legal impacts that lead to downstream problems related to immigration violations in maritime zones due to the lack of zoning regulations. Therefore, constructive legal and policy formulations are needed to serve as a fundamental foundation for projecting a comprehensive immigration oversight mechanism in Indonesia's maritime zones.